The relationship of urban farming with horticultural therapy for urbanites: a systematic review / Nurul Raihana Ramzi ... [et al.] - Ramzi, Nurul Raihana; Ahmad, Che Bon; Hamzah, Helmi; Othman, Noriah (UiTM Press, 2024)
Urbanisation has increased stress levels, which has resulted in social issues that are expected to worsen in the future. Under these circumstances, it is believed that "horticultural therapy", an activity with diverse plant life, is very helpful in reducing physical and mental stress. Meanwhile the term "urban farming" in this context refers to the expansion of agricultural products inside of cities which increases options for people to access healthy and fresh food. Thus, believed to improve people's health and well-being by fostering interactions between people and plants. The relationship between urban farming and horticultural therapy to reduce urban stress is discussed in this paper, which explore the articles published in SCOPUS between year 2010 and year 2022. A systematic approach using PRISMA software was used to addresses data identification, evaluation, exclusion, and inclusion. Results showed the effects of horticultural therapy with urban farming elements were associated with more than one (1) horticultural therapy interaction, where a nature-based element was a potential source of viable and significant outcomes. Hence, this exploration emphasised the value of fostering horticulture therapy connections with urban farming. This review formulated the preliminary conceptual framework of the relationship of urban farming and horticultural therapy to reduce urban stress. It shows a constructive interaction between urban farming and horticultural therapy as the potential constructs to reduce urban stress (improves mental and physical health). This conceptual framework will be used as the basis for further research undertaking.